Deletion of Pregnancy Zone Protein and Murinoglobulin-1 Restricts the Pathogenesis of West Nile Virus Infection in Mice - Krause, Keeton; Azouz, Francine; Nakano, Eileen; Nerurkar, Vivek R.; Kumar, Mukesh (Frontiers in Microbiology, 2019)
West Nile virus (WNV) is an enveloped positive-stranded RNA virus that causes meningitis, encephalitis, and acute flaccid paralysis in humans. There are no therapeutic agents available for use against WNV infection. Alpha-2 macroglobulin (A2M) is a major plasma proteinase inhibitor that also has important role in immune modulation. In mice, pregnancy zone protein (PZP) and murinoglobulin-1 (MUG-1) are two close homologous of human A2M. In this study, we investigated the role of PZP and MUG-1 proteins in the pathogenesis of WNV infection in mice. Adult C57BL/6J wild-type and PZP/MUG-1 double knockout (DKO) mice were inoculated subcutaneously with WNV and mortality, virus burden, and immune responses were analyzed. Infection of wild-type (WT) mice with WNV resulted in significantly high morbidity and mortality. In comparison, no mortality was observed in DKO mice, suggesting that PZP and MUG-1 play a deleterious role in WNV infection. Increased survival in WNV-infected DKO mice was associated with significantly low viral burden in serum, spleen, kidney and brain compared to WT mice. In addition, significantly reduced levels of type 1 interferon and WNV-specific antibodies were observed in the DKO mice compared to WT mice. We further demonstrated that protein levels of inflammatory cytokines and chemokines in the serum, spleen and brain were significantly reduced in DKO mice compared to WT mice. Collectively our data demonstrate that lack of PZP and MUG-1 restricts the pathogenesis of WNV infection in mice.